(3MSf GdeMGVQI aj CNHGQ eUQ hGdbGgQIs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPi aGhJ Hjf GdYHGO , haVd HYV Ndbg Ydi HYV MJi ai GdCecfI hGdHdGO gPG cJGH SejJg MSf GdeMGVQI ai CNHGQ eUQ hGdbGgQI , hChQOJ ajg ahGFO SfjI s
(3BNQgG (B:s
(3cCfg HjV OLGL hbO dWNgG GdcGJH HGdRYaQGf BNQ MSf GdeMGVQI s
(3HgG fXGe GdJYbjHIs
(3HChdgG agQS ddehVhYGJ MOjKs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B535s
Keywords: (3GdJGQjNs